Microbiome‐within‐a‐Membrane: A Microfluidic‐Based Model for Spatially Constrained Culture of Intestinal Microbiota (Adv. Funct. Mater. 48/2018). (26th November 2018) - Pajoumshariati, Seyed Ramin; Azizi, Morteza; Zhang, Shiying; Dogan, Belgin; Simpson, Kenneth W.; Abbaspourrad, Alireza
Abstract : Inflammatory bowel disease is linked to complex interactions with the intestinal microbiome. In article number1805568, Alireza Abbaspourrad and co‐workers introduce a microfluidic approach to embed viable bacteria in microfiber for co‐culturing human enteric microbes. This approach is an important step toward a realistic in‐vitro model of the human intestinal microbiome, paving the way to in‐depth in‐vitro studies of related diseases.